2003
DOI: 10.1034/j.1399-3046.2003.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus‐based immunosuppression with steroid withdrawal in pediatric kidney transplantation – 4‐year experience at a moderate‐volume center

Abstract: Tacrolimus-based immunosuppression with steroid withdrawal in pediatric kidney transplantation was pioneered at the University of Pittsburgh but is not broadly practiced at other centers. We present our 4-year experience with a modified Pittsburgh protocol at our own moderate-volume center. Seventeen pediatric kidney transplant recipients were treated with a tacrolimus-based immunosuppressive regimen involving steroid withdrawal over 6-12 post-transplant months in most cases and followed for up to 49 months. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…With the advent of tacrolimus, improved graft outcomes and decreased rates of rejection have been demonstrated both in adult and pediatric populations (16,17). This heralded the successful implementation of steroid withdrawal in clinically stable pediatric kidney transplant recipients (18,19) followed by the development of steroid-avoidance protocols (5-9). Furthermore, a recent Cochrane meta-analysis of adult randomized controlled trials demonstrated that there was no increased risk of acute rejection or graft loss in steroidsparing regimens that used tacrolimus for baseline maintenance immunosuppression (20).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of tacrolimus, improved graft outcomes and decreased rates of rejection have been demonstrated both in adult and pediatric populations (16,17). This heralded the successful implementation of steroid withdrawal in clinically stable pediatric kidney transplant recipients (18,19) followed by the development of steroid-avoidance protocols (5-9). Furthermore, a recent Cochrane meta-analysis of adult randomized controlled trials demonstrated that there was no increased risk of acute rejection or graft loss in steroidsparing regimens that used tacrolimus for baseline maintenance immunosuppression (20).…”
Section: Discussionmentioning
confidence: 99%
“…Reliable prevention of acute rejection resulted, as well as reduction in the use of steroids. [8][9][10][11][12][13] However, the drastic weaning from immunosuppression accomplished in the early cases was almost never accomplished. Efforts to improve the complex protocols were frustrated for many years because the mechanisms of organ engraftment, and the effect of immunosuppression on these mechanisms, were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimusbased immunosuppression has proven efficacy in reducing graft rejection and minimizing adverse events in pediatric patients undergoing renal transplantation (2)(3)(4)(5)(6). In an effort to expand the options for effective and safe prophylaxis against early rejection, there has been investigation into new adjunctive immunosuppressants such as the interleukin-2 receptor antagonists (IL-2 Ra).…”
Section: Introductionmentioning
confidence: 99%